Avaliação do desempenho cognitivo e transtornos mentais em pacientes obesos - Mazon, Janaina Niero (2017)
Introduction: Obesity is characterized as a serious public health problem, since it is a chronic, multifactorial disease associated with the development of several comorbidities. The pathophysiology of obesity includes alterations in the peripheral tissues and also in the Central Nervous System (CNS); such as the hypothalamus, hippocampus, and prefrontal cortex, which relate respectively to the center of satiety, memory and learning, and the reward system. In this context, it is necessary to seek to understand the relationship between obesity and cognitive impairment and mental disorders, such as anxiety and depression. Objective: To analyze the relationship between cognitive performance and mental disorders in obese and eutrophic patients. Methodology: Control case study, in which 30 obese patients (BMI> 30) and 30 eutrophic patients (BMI <30) were evaluated. The case group and the control group participated in the application of a socio-demographic questionnaire, three cognitive evaluation tests: Digits, Sequence of Numbers and Letters and Wasi, which aimed to measure the Intellectual Quotient (IQ) and answered an inventory of anxiety and of depression. The control group was matched according to age, sex and schooling. Both results were compared and analyzed between groups. Results: Obese patients presented a higher score in the digit tests and Wasi test. There was no statistical difference between the groups in the test sequence of numbers and letters. Patients in the obese group had higher scores on the anxiety and depression inventory scores compared to the eutrophic group. Conclusion: Obesity is related to a lower performance in cognitive tests and an increase in the symptoms of anxiety and depression.